Tourism brochures' images : a reading by Achenese - Fitri Anti binti Abubakar
After the 2004 tsunami, the Aceh provincial government (APG) was given more opportunities to produce its own project, namely meaning-making which is in accordance with Aceh values and traditions. One such project was to construct the image of new Aceh via touristic brochures. However, do the citizens of Aceh or people of Banda Aceh in particular, agree or reject the produced construction of reality? Using the Stuart Hall's theory of reading, this work investigates the convergence and divergence of reality on Aceh, in relation to the producer (APG) versus the readers (the people of Banda Aceh). Methodologically, vignettes in the form of the published touristic images were used as a device in the interviewing process to collect the data. A content analysis findings showed that the majority of readers were 'preferred' readers. Mosques as the preferred artifacts were clearly shown in the imagination and the fantasy of both the producer and the readers. Islam as a way of constructed reality is succinctly clear in Aceh.